2016
DOI: 10.3390/ijms17030384
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of G0/G1 Switch Gene 2 in Adipose Tissue of Transgenic Quail Inhibits Lipolysis Associated with Egg Laying

Abstract: Abstract:In avians, yolk synthesis is regulated by incorporation of portomicrons from the diet, transport of lipoproteins from the liver, and release of lipids from adipose tissue; however, the extent to which lipolysis in adipose tissue contributes to yolk synthesis and egg production has yet to be elucidated. G0/G1 switch gene 2 (G0S2) is known to bind and inhibit adipose triglyceride lipase (ATGL), the rate-limiting enzyme in lipolysis. The objective of this study was to determine whether overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The specific pattern of gene expression in certain types of cells, particular developmental stages, and nutritional conditions has been shown to be regulated by conserved regulatory elements, including a promoter region found in previous studies along with our reports [ 4 , 5 , 19 , 20 , 21 ]. In the current study, conserved promoter regions were identified in the chicken MUC2 gene that are specifically expressed in intestinal tissues of 7-week-old broiler chickens.…”
Section: Discussionsupporting
confidence: 83%
“…The specific pattern of gene expression in certain types of cells, particular developmental stages, and nutritional conditions has been shown to be regulated by conserved regulatory elements, including a promoter region found in previous studies along with our reports [ 4 , 5 , 19 , 20 , 21 ]. In the current study, conserved promoter regions were identified in the chicken MUC2 gene that are specifically expressed in intestinal tissues of 7-week-old broiler chickens.…”
Section: Discussionsupporting
confidence: 83%
“…Apo very low density lipoprotein II (APOVLDL-II) is related to the secretion of VLDL, which plays a pivotal role in egg formation (19). The described changes in the fat pad and ATGL expression found in the study by Chen et al (40) were also observed in our study ( Fig. 1-III ).…”
Section: Discussionsupporting
confidence: 91%
“…As we know that both fatty acid and cholesterol metabolism are involved in the regulation of egg formation (40, 41), and lipid mobilization from the adipose tissue is one of the main sources supporting the onset of egg production. As a result of lipid mobilization, the increase in the fat pad is the most intuitive indication of a supply of raw material available for egg production (42).…”
Section: Discussionmentioning
confidence: 99%
“…In mammal, adipose triglyceride lipases (ATGLs) play critical roles in TAG mobilization, and ATGL mutation results in the accumulation of TAG and FAs in plasma (Zechner et al, 2007 ). In Japanese quail , ATGL knockdown shifts the balance toward a net accumulation of TAG in fat tissues and reduces number of eggs (Chen et al, 2016 ). At least two kinds of lipases have been documented to play important roles in the maintenance of insect lipid homeostasis by regulating lipolysis in the fat body.…”
Section: Introductionmentioning
confidence: 99%